Perspectivas sobre as tecnologias em um projeto transdisciplinar - Almeida, Rodolfo Carli de (2016)
This dissertation investigated the prospects of technologies in a transdisciplinary project, with the main theme environment, running on a mid-level technical school class. Initially, extensive research on the subject transdisciplinary was necessary, trying to understand how was the fragmentation of knowledge across disciplines, the origin and motives of transdisciplinary look and pedagogical alternatives for understanding the contemporary educational scene. Next, we discuss the meeting of teacher training with the use of technology in the situations experienced during the professional practice. There was also the assessment of the technological resources available in school, the study of technology insertion of reasons the current curriculum and verification of how the use of technology in the knowledge construction process is planned. We define the Participant search method that allowed us to find ways to plan actions and observe the results on the transdisciplinary perspective. The research consisted of several actions, among them, a visit to a social and environmental inclusion program, participation in Environment Week on campus and four visits in natural environments with activities planned for the technology was present as a mediator, facilitator and bridge to interaction teacher x student. We use a search form structured to collect direct data and information on social networks of students who showed us how these young people interact with the school and with the world through technology. Made photographic records showing all phases and materialize the sense of inclusion of human with nature. Dialogue and participation of teachers and observation of the interaction of students with research, observe their perceptions of the meaning production with the use of technologies and present the data so that the reader is able to find other senses experience. It is concluded that there are indications pointing to a targeted education for environmental awareness must be present from teacher training, with the possibility of mediation through technology. Where it is not possible at this early point, at least to happen in training format. Thus, we present, from the survey, a transformer looking for an education that, using the mediation of technology, sees social problems and propose exits from a transdisciplinary look.